2020
DOI: 10.33545/gynae.2020.v4.i3c.595
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of iron sucrose versus ferric Carboxymaltose in the management of iron deficiency Anaemia in pregnancy

Abstract: Iron deficiency anemia is the most common hematological but manageable health problem encountered among the pregnant women globally but more common in developing countries like India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…31 Similar studies by Naqash et al, Agrawal et al, Mahaur et al and Patel et al evaluating the efficacy and safety of FCM in comparison to IS in treatment of moderate to severe anemia in Indian pregnant women, concluded FCM was more effective and safer compared to IS. [33][34][35][36] Similar findings were reported in our study. Pregnant women with moderate to severe anemia reporting in third trimester, always pose a clinical challenge as there is significant risk of impaired cardiovascular function, compromised immunity, premature delivery, low birth weight and intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 92%
“…31 Similar studies by Naqash et al, Agrawal et al, Mahaur et al and Patel et al evaluating the efficacy and safety of FCM in comparison to IS in treatment of moderate to severe anemia in Indian pregnant women, concluded FCM was more effective and safer compared to IS. [33][34][35][36] Similar findings were reported in our study. Pregnant women with moderate to severe anemia reporting in third trimester, always pose a clinical challenge as there is significant risk of impaired cardiovascular function, compromised immunity, premature delivery, low birth weight and intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 92%
“…17 In our study anemia was more common in Multigravida than in Primigravida (Group I-70%; Group II-58%). The findings were consistent with results obtained in study by, Patel Alpesh et al, Deepali Janugade, Khan S and Gupta S. A., Mahaur B et al and Beigh et al [11][12][13]17,18 Sunil et al found that 44% of patients in FCM group and 38% in Iron Sucrose group were Primigravida, while 56% of patients in FCM group and 62% in Iron Sucrose group were multigravida. 14 In the study conducted by Metgud MC et al, 56.86% of females were multigravida in FCM group and 76.9% in the Iron sucrose group.…”
Section: Discussionsupporting
confidence: 47%
“…Compared to other parenteral iron preparations, FCM has an excellent safety profile in pregnancy [ 25 ], with no [ 14 ] or minimal mild adverse effects reported by fewer patients [ 12 , 15 , 16 , 23 , 24 ]. The most common adverse effects reported, usually after ≥2 FCM doses are headache, mild local reaction, nausea, dizziness, abdominal pain, constipation, and fever and chills [ 12 , 15 , 16 , 23 , 24 ]. The present subgroup analysis also reported minimal adverse effects in 8.6% of study population which is in line with the published data.…”
Section: Discussionmentioning
confidence: 99%
“…Tere is abundant clinical evidence supporting the effective and safe use of IV FCM for correcting anemia and replenishing iron stores during pregnancy [12][13][14][15][16][17][18][19][20][21][22][23][24]. Also, compared to other parenteral iron preparations, IV FCM reported rapid correction of anemia during pregnancy [12][13][14][15][16][17][18][19][20][21][22][23][24]. Further, a large FCM dose (1000 mg) can be administered in a single setting with good efcacy and minimal adverse efects [12, 14-16, 21, 23, 24, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation